Transformational school leadership as a key factor for teachers' job attitudes during their first year in the profession. (January 2020) - Thomas, Laura; Tuytens, Melissa; Devos, Geert; Kelchtermans, Geert; Vanderlinde, Ruben
Teacher attrition is a global concern that is particularly prevalent among beginning teachers. Teachers' intrinsic motivation to teach, affective organisational commitment and job satisfaction are considered job attitudes that stop them from dropping out of the profession. This study explores the interplay between factors at the school level (i.e. transformational leadership of the principal, professional collegial support) and the teacher level (i.e. self-efficacy) influencing these job attitudes. A sample of 292 first-year primary-school teachers participated. The results of the path analysis demonstrated that transformational leadership of the principal is directly related to teachers' job attitudes in a positive way. Moreover, transformational leadership of the principal is also indirectly related to these attitudes, via both professional collegial support and teachers' self-efficacy. Implications for the supportive role of the principal in the teachers' first year in the profession are discussed.